Returns to education in Greece: Causal evidence from the 1977 labor market survey - Harry Anthony Patrinos (Global Labor Organization (GLO), 2025)
We estimate the causal effect of schooling on log earnings using instrumental variables (IV), addressing the endogeneity of schooling by using father's education as an instrument. The IV estimate implies a return of approximately 7.7 percent per additional year of schooling. First-stage and endogeneity tests confirm instrument strength and the need for IV.
Keywords: I2; I26; J24; J31; 330; Returns to education; Instrumental Variables; Causal impact